3D nanocomposites of β-TCP-H3BO3-Cu with improved mechanical and biological performances for bone regeneration applications - Sarvesh Kumar Avinashi; Rajat Kumar Mishra; Shweta; Saurabh Kumar; Amreen Shamsad; Shama Parveen; Surajita Sahu; Savita Kumari; Zaireen Fatima; Sachin Kumar Yadav; Monisha Banerjee; Monalisa Mishra; et al. (Scientific Reports)
Abstract Recently, 3-D porous architecture of the composites play a key role in cell proliferation, bone regeneration, and anticancer activities. The osteoinductive and osteoconductive properties of β-TCP allow for the complete repair of numerous bone defects. Herein, β-TCP was synthesized by wet chemical precipitation route, and their 3-D porous composites with H3BO3 and Cu nanoparticles were prepared by the solid-state reaction method with improved mechanical and biological performances. Several characterization techniques have been used to investigate the various characteristics of fabricated porous composites. SEM and TEM studies revealed the porous morphology and hexagonal sheets of the β-TCP for the composite THC8 (82TCP-10H3BO3-8Cu). Moreover, the mechanical study showed excellent compressive strength (188 MPa), a high Young’s modulus (2.84 GPa), and elevated fracture toughness (9.11 MPa.m1/2). An in vitro study by MTT assay on osteoblast (MG-63) cells demonstrated no or minimal cytotoxicity at the higher concentration, 100 µg/ml after 24 h and it was found a more pronounced result at 20 µg/ml on increasing the concentration of Cu nanoparticles after incubating 72 h. The THC12 composite showed the highest antibacterial potency exclusively against B. subtilis. S. pyogene, S. typhi and E. coli. at 10 mg/ml, indicating its potential effectiveness in inhibiting all of these pathogens. Genotoxicity and cytotoxicity tests were also performed on rearing Drosophila melanogaster, and these findings did not detect any trypan blue-positive staining, which further recommended that the existence of composites did not harm the larval gut. Therefore, the fabricated porous composites THC8 and THC12 are suitable for bone regrowth without harming the surrounding cells and protect against bacterial infections.